UPAYA MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK MENGGUNAKAN MEDIA CROSSWORD PUZZLE DALAM PROSES EVALUASI PADA MATA PELAJARAN AKIDAH AKHLAK - Pasya, Rayi; Darisman, Dede (Jurnal Penelitian Pendidikan Islam, 2017)
The writing is based on the low learning achievement of students of class IV MIS Cileungsir on learning Akidah Akhlak. As an effort to improve students' learning achievement, researchers use Crossword Puzzle media. After doing research results obtained is Student learning outcomes in cycle I reached the average value 74.12, cycle II 82.62 and cycle III 99.25 with a complete range of all learners. This proves that the improvement of student learning outcomes or learning achievement of learners can be implemented with Crossword Puzzle.